Ewolucja prawa do posiadania dowodu osobistego - Jaworska, Iga (Kwartalnik Prawa Publicznego, 2015)
On the 1st of March 2015 came into force the Law on Identity Cards, which modernized the notion of an identity card, adjusting basic Polish identity card to EU standards. Using this moment the author decided to represent in the article the evolution of the right to have an identity card, discussing key legislation associated with its history. Noted the changing legal nature of this document and assessed the adopted legal structure.